2011
DOI: 10.22201/ib.20078706e.2011.3.739
|View full text |Cite
|
Sign up to set email alerts
|

Aspectos biológicos del pleco invasor Pterygoplichthys pardalis (Teleostei: Loricariidae) en el río Palizada, Campeche, México

Abstract: Resumen. Se analizó el comportamiento de la abundancia, la relación peso-longitud y el índice gonadosomático de Pterygoplichthys pardalis en el río Palizada en Campeche, México. Se realizaron muestreos mensuales de junio de 2008 a mayo de 2009 con redes agalleras. Se colectaron 118 plecos cuyas tallas estuvieron entre 222 y 422.5 mm de longitud total (LT) y un peso de 72.8 a 385.4 g. El periodo de mayor abundancia se presentó de junio a agosto, no hubo diferencias significativas de la abundancia en diferentes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 17 publications
1
5
0
Order By: Relevance
“…The Lake Bacalar water basin has been recognized as one of the hydrological basins with highest priority for conservation by the Mexican National Commission for the Use and Knowledge of the Biodiversity (CONABIO) [79]. Fortunately, most wetlands and lakes in this region are relatively pristine, excepting the Hondo River on the border between Mexico and Belize, which has been heavily impacted by the discharge of organic waste and pesticides, by vegetation clearing, and by the introduction of invasive such as tilapia [80], and the Amazon sailfin catfish ( Pterygoplichthys pardalis ), which was recently detected [59,81,82] near La Unión [59]. The impact of this declining water quality and the rising incidence of invasive species on the native fish fauna needs to be carefully monitored and eDNA-based studies could provide a cost-effective way to meet this need.…”
Section: Discussionmentioning
confidence: 99%
“…The Lake Bacalar water basin has been recognized as one of the hydrological basins with highest priority for conservation by the Mexican National Commission for the Use and Knowledge of the Biodiversity (CONABIO) [79]. Fortunately, most wetlands and lakes in this region are relatively pristine, excepting the Hondo River on the border between Mexico and Belize, which has been heavily impacted by the discharge of organic waste and pesticides, by vegetation clearing, and by the introduction of invasive such as tilapia [80], and the Amazon sailfin catfish ( Pterygoplichthys pardalis ), which was recently detected [59,81,82] near La Unión [59]. The impact of this declining water quality and the rising incidence of invasive species on the native fish fauna needs to be carefully monitored and eDNA-based studies could provide a cost-effective way to meet this need.…”
Section: Discussionmentioning
confidence: 99%
“…Records have been reported from Texas, Nevada and Florida, USA (Fuller et al, 1999;Capps, 2008, Gibbs et al, 2008Pound et al, 2011), Puerto Rico (Bunkled-Williams et al, 1994), Taiwan (Liang et al, 2005(Liang et al, , 2006, the Philippines (Chávez et al, 2006), Vietnam (Levin et al, 2008), Java and Australia (Capps, 2008), Bangladesh (Hoosain et al, 2008), Turkey (Ozdilek, 2007), Poland (Keszka et al, 2008) and Italy (Piazzini et al, 2010); a recent Danube invasion has also been reported (Simonovic et al, 2011). Several studies report the invasion of loricariids in Mexico (Guzman and Barragan, 1997;Mendoza et al, 2007;Okolodkov et al, 2007;Wakida-Kusonoki et al, 2007;Wakida-Kusunoki and Amador-del Angel, 2008;Capps et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In Mexico, the sailfin catfish was detected for the first time in the Mezcala River, Guerrero (Balsas Basin), in 1995 (Guzmán and Barragán, 1997) and later in Tecpatan, Chiapas, the surroundings of Villahermosa, Tabasco (Mendoza et al, 2007), and in the Grijalva-Usumacinta Basin (Tabasco and Chiapas) (Wakida-Kusunoki et al, 2007;Wakida-Kusunoki and Amador del-Angel, 2008). The first specimens were identified as Liposarcus multiradiatus, a synonym of Pterygoplichthys multiradiatus (Armbruster, 2004); however, the species is currently identified as P. disjunctivus (Armbruster pers.…”
Section: Introductionmentioning
confidence: 99%
“…The Lake Bacalar water basin has been recognized as one of the hydrological basins with high priority for conservation by the Mexican National Commission for the Use and Knowledge of the Biodiversity (CONABIO) [75]. Fortunately, most wetlands and lakes in this region are relatively pristine, excepting the Hondo Riveron the border between Mexico and Belize, which has been heavily impacted by the discharge of organic waste and pesticides, by vegetation clearing, and by the introduction of invasive such as tilapia [76], and the Amazon sailfin catfish ( Pterygoplichthys pardalis ), which was recently detected [77,78] near La Unión [79]. The impact of this declining water quality and rising incidence of invasive species on the native fish fauna needs to be carefully monitored and eDNA-based studies could provide a cost-effective way to meet this need…”
Section: Discussionmentioning
confidence: 99%